'Throw one out that's problematic': performing authority and affiliation in design education. Issue 1 (2nd April 2016) - Oak, Arlene; Lloyd, Peter
Abstract: This paper explores interaction in graduate-level industrial design education. We outline two instances of how design reviews are conducted through social contexts and provide a theorised analysis of these instances. In particular, this paper considers how participants in a design review – both an instructor and students – enact aspects of role-oriented authority and affiliation within the context of the review. Through perspectives associated with ethnomethodology and conversation analysis, this paper discusses how a misunderstanding and a request (and the response to that request) are managed through speech, gesture, and gaze direction. We explore how the interactive, co-presence of an instructor and students impacts upon the overall performance of the review and show how some of the pedagogic practices of design education are enacted through the contexts of discourse and embodiment. This paper provides opportunities for design instructors, students, professionals and researchers to reflect upon the collaborative micro-activities of design education and to consider the impact that these may have upon participants' experiences and perceptions of design education.